Election Night at Bruce Bronzan State Assembly Campaign Headquarters in Roos-Atkins Building - Watkins, Howard::::::::: (1978)
Linda Bronzan, Bruce Bronzan, Christine Watkins, Nick Bronzan, Doug Jones watching election returns